Reframing Genetic Engineering Patents Through the Lens of Hisbah: Harmonizing Innovation and Ethical Values - Disemadi, Hari Sutra; Habidin, Nurul Fadly; Fitri, Winda; Rusdiana, Shelvi; Febriyani, Emiliya (al-'adalah, 2025)
Genetic engineering raises complex ethical and legal challenges, particularly in Indonesia, where intellectual property rights intersect with religious values. This research identifies the regulatory gap within Indonesian patent law, which lacks clear provisions for managing ethical concerns related to genetic engineering, including antitrust measures and scientific scrutiny. The study aims to explore whether the concept of Hisbah within Sharia can offer a normative framework to address these challenges while fostering scientific progress. Utilizing a normative legal research method, this study critically analyzes Law No. 13 of 2016 on Patents alongside Islamic legal doctrines. The findings reveal that, contrary to ultraconservative views, Hisbah encourages scientific advancements such as genetic engineering when aligned with societal welfare and ethical considerations, emphasizing that knowledge should contribute to the public good without enabling monopolistic practices. This research concludes that integrating Hisbah into Indonesia’s patent regulation can guide the ethical development of genetic engineering while respecting both the need for innovation and the values embedded in Indonesian society. It offers a significant perspective for policymakers to harmonize intellectual property law with Islamic principles, ensuring a balanced legal framework that safeguards public interest while promoting scientific progress.